Digital Literacy and Active Citizenship: Strengthening Participatory Democracy on Social Media - Muhammad Rahman Syah Putra; Aldi Maulana; Hafizorrahman; Marshanda Putri (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2025)
The rapid development of digital technology, particularly social media, has transformed the landscape of communication and public participation in Indonesia. Social media has now become a primary platform for the dissemination of information, political discussion, and expression—especially among the younger generation. However, behind its positive potential as a tool for digital democracy, there are serious challenges such as the spread of hoaxes, hate speech, and opinion polarization due to low levels of digital literacy. This study aims to analyze the role of digital literacy in promoting active citizenship and strengthening participatory democracy on virtual social platforms. Using a qualitative literature study method, this research examines how improving digital literacy can equip society—particularly first-time voters—to identify false information, engage constructively in political discourse, and take an active role in preventing the spread of disinformation. The findings show that adequate digital literacy is key to creating a healthy democratic space, where citizens can interact critically, responsibly, and inclusively, thereby supporting the realization of a welfare state and national resilience.